Modern Methods of Rejuvenation in Aesthetic Cosmetology - Nargis Shukurova (Scientific Trends, 2024)
The article discusses the latest minimally invasive methods of cosmetic aesthetic rejuvenation, including biorevitalization, mesotherapy, peels, botulinum therapy, dermal fillers and mesomelites, using a combined approach. This makes it possible to improve the degenerative symptoms of aging at different levels of exposure, from the skin to the facial muscles. With the help of complementary techniques (botulinum therapy, dermal fillers, mesoniti, mesotherapy, surface chemical peels), it is possible to significantly increase the satisfaction of patients and doctors.
Keywords: cosmetic aesthetics, minimally invasive rejuvenation methods.